METAFORA LAKOFF DAN JOHNSON DALAM SURAT KABAR BILD - RIZAL AKBAR, MUHAMAD (IDENTITAET, 2016)
This reseach discusses the conceptual metaphors and the kinds of metaphor contained in the Bild newspaper. The data use in this paper are metaphorical expression or linguistics metaphors in German, from the following sources of political news article entitled ISIS - Terroristen in the German daily newspaper Bild. I use the metaphor theory proposed by Lakoff & Johnson to describe the conceptual metaphors and the kinds of metaphor. I use qualitative descriptive method in this research. Various conceptual metaphors found in the results of this research, which shows that in the talks about terror, not only refer to the concepts of crime. This proves that the metaphor is a tool to give more impression to the readers. The results also show that the kind of metaphor that most often appear in Bild is structural metaphor, it’s linear with the characteristics of newspaper text that is easy, concise, clear, and precise. Keywords: conceptual metaphors, newspaper,  source target.